The interiorization of Brazilian violence, policing, and economic growth - Geoffrey M. Steeves; Francis Carlo Petterini; Guilherme V. Moura (EconomiA, 2015)
Brazilian homicide rates are among the highest in the world, inclusive of actual war zones. However, the character of Brazil's violence is changing. Recent analyses highlight a trend of dispersion of violence such that homicide rates in urban areas, traditionally the most violent places, have stagnated and declined while smaller cities and rural areas experienced a marked increase. An incipient explanation is that this trend is related to greater economic dynamism in the smaller cities, unaccompanied by increased policing. This article's empirical analysis uses locational Hoover indexes to express the dispersions of violence and economic activity, and also generates a proxy to measure the geographic concentration of police forces. Using panel data across all 26 states from 1995 to 2011, we find evidence of a correlation between dispersion of violence and GDP to less urban areas, and ambiguous results regarding police concentration. – – As taxas de homicídio do Brasil est\~ao entre as mais altas do mundo, inclusive das atuais zonas de guerra. No entanto, o caráter dessa violência está mudando. Análises recentes destacam uma tendência de dispers\~ao de violência, de forma que as taxas de homicídio em áreas urbanas, tradicionalmente os lugares mais violentos, estagnaram e declinaram, enquanto cidades menores e áreas rurais experimentaram um aumento acentuado. Uma explicaç\~ao incipiente é que esta tendência está relacionada com um maior dinamismo econômico nas cidades menores, sem haver um aumento do efetivo policial. A análise empírica deste artigo utiliza índices locacionais de Hoover para expressar as dispers\~oes da violência e da atividade econômica, e também um indicador para medir a concentraç\~ao geográfica das forças policiais. Usando dados de um painel dos 26 estados brasileiros entre 1995-2011, encontram-se evidências de uma correlaç\~ao entre a dispers\~ao da violência e do PIB para as áreas menos urbanas, e alguns resultados ambíguos em relaç\~ao à concentraç\~ao da polícia
Keywords: K42; R58; 330; Homicides; Violence dissemination; Hoover index